TOURISM AND CULTURE MINISTER TO OFFICIATE KEDAH TUA INTERNATIONAL CONFERENCE - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 18 May 2016 – The Minister of Tourism and Culture, Dato’ Seri Mohamed Nazri Abdul Aziz will officiate at the opening ceremony of the Kedah Tua International Conference 2016 (KTIC’2016) which would be held from 21 - 22 May 2016 at Park Avenue Hotel, Sg. Petani, Kedah.